A Comprehensive Analysis of E.H. Sutherland’s Theory of Differential Association in Relation to Buddhist Philosophical Teachings and Principles - Niwantha, Haputhanthrige Pathum; Rathnayake, Rathnayaka Mudiyanselage Vihangi Sandagomi (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 4 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
This study provides a comparative analysis of E.H. Sutherland’s Theory of Differential Association and Buddhist philosophical teachings, exploring their intersecting perspectives on human behaviour. Sutherland’s theory, a foundational concept in criminology, emphasises that criminal behaviour is learnt through interactions and associations within intimate social groups. Contrastingly, Buddhist principles focus on ethical and moral cultivation, highlighting the significance of virtuous conduct and spiritual development. The research employs a systematic literature review methodology to investigate three central Buddhist concepts: benevolent friendship (kalyāṇamittatā), which parallels the influence of intimate associations in shaping behaviour; the principles of interrelationship and mutual influence illustrated in Jataka stories, which reflect on the consequences of moral and immoral actions; and the causes and conditions influencing individual behaviour as articulated in Buddhist sutras, particularly the doctrine of Dependent Origination (Paticca Samuppada). The analysis reveals both congruence and divergence between the two frameworks. Both emphasise the pivotal role of interpersonal relationships in shaping behaviour, yet they differ in scope and orientation. Sutherland’s theory adopts a sociological and descriptive approach to explain how behaviour, including criminal tendencies, is socially earned. In contrast, Buddhist teachings provide a normative and prescriptive framework aimed at fostering ethical transformation and spiritual liberation. This study contributes to the interdisciplinary dialogue between criminology and philosophy, suggesting that integrating insights from Buddhist principles could offer a more comprehensive understanding of behavioural development and reformative practices.